POPULATION DYNAMICS OF HETEROTROPHS AND AUTOTROPHS BACTERIA ON SLUDGE PRODUCED WATER (CASE STUDY : OIL AND GAS EXPLORATION OF PT X) - PRAVITA SARI, EKA
Abstract: Sludge produced water from biological process been active microbes biomass in form of floc, it is expected organic content more than 50 percent. Microbial population dynamics was be done based on carbon source thats group of heterotrophs and autotrophs bacteria in the process of degrades sludge produced water. The process performance in aerobic and anaerobic until Corganic content >15% and C/N ratio 15? C/N?25 which refers in Permentan No.70/Permentan/SR.140/10/2011. Variations of process with addition of sawdust and dried leaves as bulking agent. Research study more targeted relations of population dynamics both two groups microbes with reactor performance. The growth of heterotrophs and autotrophs bacteria occur sequentially. The addition of sawdust as bulking agent give better results in sludge produced water treatment. Highest population of heterotrophs aerobic bacteria 4.9.1013 CFU/g soil (20th day), population of autotrophs aerobic bacteria 8.3.108 CFU/g soil (30th day), population of heterotrophs anaerobic bacteria 1.56.108 CFU/g soil (25th day), and population of autotrophs anaerobic bacteria 9.7.105 CFU/g soil (40th day). Optimum reactors was found in RA2 (for heterotrophs aerobic bacteria) with ? is 0.807 time-1. RA3 (for autotrophs aerobic bacteria) with ? is 0.468 time-1, RN1 (for heterotrophs anaerobic bacteria) with ? is 0.412 time-1, and RN5 (for autotrophs anaerobic bacteria) with ? is 0.197 time-1. The identification obtained is group of nitrogen fixer from Bacillus, Pseudomonas and Clostridium. Bacillus groups such as B.polymyxa, B.licheniformis, B.circulans, B.lentus, B.megaterium dan B.coagulans and Clostridium groups such as Clostridium sordelii and Clostridium beijerinckii.